In Search of a Soul: Religion and National Integration - Padiyath, Thomas (Journal of Dharma, 2008)
Thinking about the current socio-religious and political scenario of India, I feel that the reverse is true that the body of ‘Bharath Matha’ is in search of her (lost) soul! Two powerful institutions that determine the course of any country or, broadly put, the very course of world history, are religion and politics. Indian history is no exception to it. Perhaps India may be one of the rarest countries where we see this influence very much, although it is not the same as how religion and politics influence the destiny of her neighbouring countries like Pakistan, Afghanistan, Bangladesh, or Nepal.